Penguatan Nilai-Nilai Karakter Islami Melalui Implementasi Program Tahfidz Al-Qur’an Di Sdit Umar Bin Khattab Kudus - Ainur Rizka Maulina; Sanusi (Edification Journal : Pendidikan Agama Islam, 2026)
The research aims to describe the implementation of the Qur’an tahfidz programme and the role of teachers in shaping students’ Islamic character at SDIT Umar bin Khattab Kudus. This research uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that the tahfidz programme is not only oriented towards achieving memorisation targets, but also a means of forming religious characters such as discipline, responsibility, honesty, and love for the Qur’an. Teachers have a central role as memorisation mentors, motivators, and role models in students’ daily behaviour. Supported by the Talaqqi and Qiraati methods, as well as routine religious practices at school, the Tahfidz program is implemented systematically. Challenges include low student motivation, limited family support, and poor time management. This study confirms that the collaboration between teachers, schools, and parents, established through practical involvement, significantly contributes to the development of students’ Islamic character through the tahfidz program.